Analysis of the Influence of Intellectual Capital, Working Capital, and Leverage in Affecting Profitability and Its Relationship on the Value of the Company - Widhiastuti, Susanti; Ekasaputra, Bobby; Jayadi, Jayadi (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2020)
This study aims to analyze the effect of intellectual capital (VAHU), working capital (working capital turnover / WCT), and leverage (DER) in influencing profitability (ROE) in relation to company value (PBV). The population in this study are companies in the mining, plantation, and consumer goods manufacturing industries listed on the Indonesia Stock Exchange from 2014 to 2018 with a total of 40 companies. The sample selection is done using the purposive sampling method and the samples used in this study were 14 companies. This type of research used in this study is a causal type of explanatory research that seeks to test the influence of variables in a structural model. The results showed that: 1). Intellectual capital affects the profitability and value of the company, 2). Working capital turnover does not affect the profitability and value of the company, 3). Time affects the profitability and value of the company, 4). Profitability affects the value of the company.